DESAIN BAHAN AJAR BERORIENTASI PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH - Indri Rochmatika (FKIP Unswagati, 2023)
This study aims to determine the development of teaching materials oriented to problem-based learning models to improve problem-solving skills. To find out student responses to module teaching materials that are oriented to problem-based learning models. Knowing the increase in students' problem-solving skills after using module teaching materials in the learning process. The sample in the study was IPS class X students at SMAN 1 Tukdana, Indramayu Regency with a total of 24 students. This research is a product development research or Research and Development (R&D). The research design that the authors use is the ADDIE development model. The results of the feasibility test showed that the module teaching materials were suitable for use in the learning process by obtaining a percentage of 89%, including the very valid category. The results of student responses to the module teaching materials were good, with a percentage of 83.38%. The N-gain results of the use of teaching materials in the learning process can increase students' problem-solving abilities by 0.49, included in the medium category, the t-test results show t_count≥t_table or 13.482 ≥ 2.093 then Ha is accepted and Ho is rejected, thus the teaching material is oriented problem-based learning can improve the problem-solving skills of class X IPS SMA Negeri 1 Tukdana, Indramayu Regency.